2020
DOI: 10.1038/s41370-020-0245-z
|View full text |Cite
|
Sign up to set email alerts
|

Density and proximity to hydraulic fracturing wells and birth outcomes in Northeastern British Columbia, Canada

Abstract: Background Hydraulic fracturing, a method used in Northeastern British Columbia (Canada) to extract natural gas, can release contaminants with potential deleterious health effects on fetal development. To date, the association between hydraulic fracturing activity and birth outcomes has not been evaluated in this region. Objective To evaluate the association between the hydraulic fracturing well density/proximity and birth outcomes (birthweight, head circumference, preterm birth and small for gestational age (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…However, there are important differences in the physical conditions (e.g., fluid pressures) and surface and subsurface activities, and studies focused on abandoned and orphaned wells are needed. Oil and gas production has been found to impact air quality through emissions of volatile organic compounds, nitrogen oxides, sulfur dioxide, ammonia, and particulate matter Jaramillo and Muller, 2016;Caron-Beaudoin et al, 2018;Caron-Beaudoin et al, 2021). To our knowledge, there is only one published study measuring air pollution from abandoned wells.…”
Section: Environmental Impacts Of Abandoned and Orphaned Wellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are important differences in the physical conditions (e.g., fluid pressures) and surface and subsurface activities, and studies focused on abandoned and orphaned wells are needed. Oil and gas production has been found to impact air quality through emissions of volatile organic compounds, nitrogen oxides, sulfur dioxide, ammonia, and particulate matter Jaramillo and Muller, 2016;Caron-Beaudoin et al, 2018;Caron-Beaudoin et al, 2021). To our knowledge, there is only one published study measuring air pollution from abandoned wells.…”
Section: Environmental Impacts Of Abandoned and Orphaned Wellsmentioning
confidence: 99%
“…A few studies have found positive associations between the proximity to shale gas development activities and birth outcomes or respiratory diagnoses (Bamber et al, 2019), while results of other studies are inclusive (Caron-Beaudoin et al, 2021). Overall, a recent review finds that "the epidemiologic literature on the potential health effects of oil and natural gas operations is still inadequate to definitively guide policy" (Bamber et al, 2019, p. 15).…”
Section: Environmental Impacts Of Abandoned and Orphaned Wellsmentioning
confidence: 99%
“…These negative effects include higher illness rates, negative birth outcomes, and other changes to morbidity and mortality when compared to areas where there is no fracking 4,5,12 . The only report evaluating such effect in Colorado found positive associations between density and proximity to natural gas wells within a 10-mile radius of maternal residence and prevalence of congenital heart disease and possibly neural tube defects 9 However, several other studies evaluating the effects of hydraulic fracturing on birth outcomes, including, birth weight in other states and Canada; have had mixed results 12,13 . The majority of studies have reported a negative association that varies in effect size [14][15][16][17] but contradictory results that include positive associations with certain caveats have also been reported in addition to Colorado 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“… 9 However, several other studies evaluating the effects of hydraulic fracturing on birth outcomes, including, birth weight in other states and Canada; have had mixed results. 12 , 13 The majority of studies have reported a negative association that varies in effect size, 14-17 but contradictory results that include positive associations with certain caveats have also been reported in addition to Colorado. 18 , 19 Birth weight of an infant is an important determinant of its chances of survival and healthy growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found higher atmospheric concentrations of ozone, fine particulates, and volatile organic compounds downwind of oil and gas wells, and contamination of ground and surface waters near wells by dissolved solids and organic compounds [3,4,6,8]. Researchers have also found that living near oil and gas wells is associated with higher risk of cardiovascular disease, impaired lung function, anxiety, depression, preterm birth, and impaired fetal growth [1,5,[10][11][12][13][14][15][16][17][18][19][20][21]. In several studies, risk was heightened among racially and socioeconomically marginalized people, and in several U.S. regions these same groups have disproportionately high exposure to wells and natural gas flaring [12,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%